Maritime Defense Strategy Education as an Effort of the Indonesian Government in Maintaining Maritime Security - Kuncoro Arry Prasetyo; Ansori Ansori; Buddy Suseto (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
To establish good maritime governance, the Indonesian government must pay attention to maritime security aspects in every maritime policy and integrate maritime security education into the national education curriculum. However, implementing the World Maritime Axis concept, the Indonesian government still needs to consider the maritime security perspective as a top priority. The ultimate goal of good maritime governance development should include the strength of the Navy as the most important supporting element and the implementation of maritime security training and education for Indonesian maritime society. This study aims to analyze the efforts of the Joko Widodo (Jokowi) administration in addressing maritime security issues through the implemented maritime security training and education programs. The research method used is qualitative descriptive by using secondary data from a literature review and interpretation found in previous journal articles, with data collection techniques through literature study. The study results indicate that addressing maritime security issues requires hard and soft efforts from the government, including implementing maritime security training and education programs for Indonesian maritime society and integrating maritime security education into the national education curriculum.